Danish for All? : Balancing Flexibility with Security; The Flexicurity Model - Zhou, Jianping (IMF Working Papers; Working Paper, 2007)
The Danish flexicurity model has attracted attention among policymakers in Europe, because it suggests that a flexible labor market can coexist with a generous welfare system to achieve low unemployment. Using a panel of 19 countries over 1960-2002, the paper identifies the elements of the flexicurity model that may have contributed to the low unemployment rate. A theoretical model of dynamic policies is constructed to analyze whether the model can be emulated by other countries. Focusing on the financing aspect, the paper finds that effective implementation will depend on the initial unemployment level and budgetary situation of the country.